2014
DOI: 10.1111/febs.13167
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐486‐5p, which is downregulated in hepatocellular carcinoma, suppresses tumor growth by targeting PIK3R1

Abstract: Deregulated microRNAs and their roles in carcinogenesis and cancer progression have attracted much attention. In previous studies conducted in our laboratory, the Illumina Solexa massively parallel signature sequencing of miRNomes in nontumor and hepatocellular carcinoma (HCC) tissues revealed that miR-486-5p was significantly downregulated in HCC, but its role in HCC development remains unknown. In this study, miR-486-5p levels in HCC tissues and matched control tissues, and in seven HCC cell lines (QGY-7701,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 40 publications
5
82
0
Order By: Relevance
“…It was previously demonstrated that the overexpression of miR-486-5p may inhibit cell proliferation, migration and invasion, and decrease tumor growth via targeting PIK3R1 and AKT in hepatocellular carcinoma (25). The results of the present study indicated that the overexpression of miR-486-5p, as simulated using the transfection of miR-486-5p mimics, inhibited cell migration and invasion.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It was previously demonstrated that the overexpression of miR-486-5p may inhibit cell proliferation, migration and invasion, and decrease tumor growth via targeting PIK3R1 and AKT in hepatocellular carcinoma (25). The results of the present study indicated that the overexpression of miR-486-5p, as simulated using the transfection of miR-486-5p mimics, inhibited cell migration and invasion.…”
Section: Discussionsupporting
confidence: 59%
“…microRNAs (miRNAs/miRs) are small, non-coding RNAs of [19][20][21][22][23][24][25] nucleotides that may negatively regulate gene expression at a transcriptional or post-transcriptional level (5). Additionally, the expression profiles of miRNAs may be more accurate in classifying subtypes of tumors compared with mRNA expression profiles (6).…”
Section: Introductionmentioning
confidence: 99%
“…2). This corroborates a recent study performed on Chinese patients in which miR-486-5p was also downregulated in HBV-induced HCC tissues (33).…”
Section: A B Discussionsupporting
confidence: 92%
“…3-5). These results are in line with those of a recent study performed on QGY-7701 and QGY-7703 HCC cell lines, which reported that miR-486-5p also repressed the migration and induced apoptosis of those types of cells (33).…”
supporting
confidence: 92%
See 1 more Smart Citation